2019
DOI: 10.1111/jcmm.14202
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Lin28‐TNFR2 signalling in cardiac stem cell activation and differentiation

Abstract: Tumour necrotic factor receptor‐2 (TNFR2) has been to be cardiac‐protective and is expressed in cardiac progenitor cells. Our goal is to define the mechanism for TNFR2‐mediated cardiac stem cell activation and differentiation. By employing a protocol of in vitro cardiac stem cell (CSC) differentiation from human inducible pluripotent stem cell (hiPSC), we show that expression of TNFR2 precedes expression of CSC markers followed by expression of mature cardiomyocyte proteins. Activation of TNFR2 by a specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The three piPSC lines could differentiate into cells with mature cardiac phenotypes that expressed cTnT and cardiac contractile protein and displayed a high percentage of spontaneous cardiac beating. Xiang et al (2019) have shown that LIN28 plays a critical role in the tumor necrosis factor receptor-2 (TNFR2)-mediated differentiation of hiPSC-derived cardiac stem cells by inducing the expression of TNFR2, which is usually found in mature cardiomyocytes, vascular endothelial cells, and hematopoietic cells. Conversely, LIN28 inhibition significantly reduced cardiac stem cell differentiation and activation ( Xiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three piPSC lines could differentiate into cells with mature cardiac phenotypes that expressed cTnT and cardiac contractile protein and displayed a high percentage of spontaneous cardiac beating. Xiang et al (2019) have shown that LIN28 plays a critical role in the tumor necrosis factor receptor-2 (TNFR2)-mediated differentiation of hiPSC-derived cardiac stem cells by inducing the expression of TNFR2, which is usually found in mature cardiomyocytes, vascular endothelial cells, and hematopoietic cells. Conversely, LIN28 inhibition significantly reduced cardiac stem cell differentiation and activation ( Xiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… Xiang et al (2019) have shown that LIN28 plays a critical role in the tumor necrosis factor receptor-2 (TNFR2)-mediated differentiation of hiPSC-derived cardiac stem cells by inducing the expression of TNFR2, which is usually found in mature cardiomyocytes, vascular endothelial cells, and hematopoietic cells. Conversely, LIN28 inhibition significantly reduced cardiac stem cell differentiation and activation ( Xiang et al, 2019 ). In summary, our study demonstrated an effective method for inducing the spontaneous differentiation of piPSCs into cardiomyocytes via EB formation.…”
Section: Discussionmentioning
confidence: 99%
“…This reprogramming is driven by the expression of LIN28, BMP10 and TCIM among others, along with the downregulation of DGKK, GRIK1 and different ion channels. Importantly, Lin28 is a primal regulator of growth and metabolism in stem cells [8], while it also protects cardiomyocytes against apoptosis and regulates cardiac progenitor activation [34,35]. We have shown upregulation of BMP10, not only transcriptionally but also at a protein level.…”
Section: Discussionmentioning
confidence: 84%
“…But even though the adult heart is mainly comprised of post-mitotic cardiomyocytes, endogenous regenerative programs can be reactivated [4,53,54] and the presence of multipotent adult cardiac stem cells opens new opportunities for therapeutic myocardial repair [55]. The reactivation of Lin28a has already proven to enhance tissue repair in adults by reprogramming cellular bioenergetics [9], as well as to activate cardiac stem cells [35]. Furthermore, a population of hypoxic cardiomyocytes displaying proliferative regenerative potential have been shown to widely contribute to new cardiomyocyte formation in the adult heart [56].…”
Section: Discussionmentioning
confidence: 99%
“…One possible process is the TNF/TNFR2 signalling, for which a cardioprotective and immunoregulatory property has been demonstrated by mounting preclinical data. 28,[48][49][50][51] Indeed, monoclonal antibodies that specifically activate TNFR2 have already been advocated as a novel therapeutic strategy for conditions including CVDs. 19,52 Given the fact that TNFR2 has higher affinity to transmembrane TNF, supressing TACE, the enzyme that truncates membrane-bound TNF into soluble cytokine, may act similarly as the TNFR2 agonists.…”
Section: Results Interpretationmentioning
confidence: 99%